Rearranged benzophenones and prenylated xanthones from Garcinia propinqua twigs - Cholpisut Tantapakul (2018)
The first phytochemical investigation of Garcinia propinqua has led to the isolation and identification of three new compounds, including two rearranged benzophenones, doitunggarcinones A (1) and B (2), and a xanthone, doitunggarcinone C (3), together with seven known compounds (4-10). The structures of 1-3 were elucidated on the basis of spectroscopic methods, including UV, IR, NMR, and MS. The antibacterial activity of the 10 isolates was evaluated against Escherichia coli TISTR 780, Salmonella typhimurium TISTR 292, Staphylococcus aureus TISTR 1466, and methicillin-resistant Staphylococcus aureus (MRSA) SK1. © 2012 The American Chemical Society and American Society of Pharmacognosy.